Chronic Calcific Pancreatitis Associated Diabetes Presenting as Involuntary Weight Loss and Multiple Soft Tissue Calcifications in a Young Male - Kant, Ravi; Sudan, Aditya (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Introduction: Chronic Calcific Pancreatitis, a rare form of secondary diabetes occurs due to recurrent alcohol induced acute pancreatitis. Case Summary: A 28 year old male patient presented with significant involuntary weight loss associat-ed with a history of passing clay colored sticky stools for the past 1 year. He was also detected to have deranged blood sugars on routine work up at a local hospital for increased thirst and increased urine output. There was a history of recurrent bouts of moderate to severe abdominal pain over the past 3 to 4 years. At the time of initial presentation his Random blood sugar values was 468 mg/dL. Other routine tests tests were within normal limits. His serum amylase levels were 185 U/L and serum Lipase levels were 467 U/L. Conclusions: Chronic fibro calcific pancreatitis is a rare cause of diabetes in young patients but has a characteristic clinical picture with a young patient presenting with features of malabsorption and low BMI, low propensity for DKA , low beta cell reserve and sensitivity to Insulin.